BASIC CONCEPTS OF EDUCATIONAL EVALUATION AND ITS IMPLICATIONS IN LEARNING ISLAMIC RELIGIOUS EDUCATION - Anugrah, Abror Dikna; Anshori, Ari (Institut Islam Mamba'ul 'Ulum Surakarta, 2024)
The use of inappropriate methods, methods of assessing learning outcomes that do not pay attention to the basic principles of assessment, inadequate management systems, leadership and unprofessional teaching staff, all hinder the success of the learning process. Learning evaluation is the main activity to determine the extent of the level of achievement of students' abilities. This step is needed because it can be used as a reference in determining a learning policy This research uses a qualitative descriptive approach and literature review method. Data collection techniques are carried out by considering various literature sources obtained from documents of various sources. . The author collects bibliographic information in the form of documents, both from books, journals, seminar results, and discussions with experts related to research. After data collection, data analysis is carried out. Evaluation includes two activities: measurement and evaluation. The hallmark of the evaluation of this process ends with the decision-making process. This decision concerns the value and usefulness of the assessment. Evaluation plays a very important role in measuring and evaluating how successful an education is. Before evaluating Islamic education, it must first be understood the nature of Islamic education itself so that the evaluation process is consistent with the field being evaluated. Learning includes aspects of planning, implementation, and evaluation. Good learning is recognized when an assessment is carried out to determine the extent to which the planned learning objectives have been achieved. In Islamic education, evaluation plays a very important role in measuring and evaluating how successful an education is. Before evaluating Islamic education, it must first be understood the nature of Islamic education itself so that the evaluation process is consistent with the field being evaluated.